Combination of torrefaction and leaching treatments on the solid biofuel characteristics of fast-growing timbers species and oil palm biomass - Lee, Chuan Li; Chin, Kit Ling; Chuah, Luqman Abdullah; Hafizuddin, Mohd Sahfani; Khoo, Pui San (North Carolina State University, 2024)
The potential of integrating acid acetic leaching and torrefaction processes was studied to create an enhanced solid biofuel from lignocellulosic biomass. The focus was on evaluating the impact of these combined methods on ash removal efficiency and the melting characteristics of the treated biomass. Two possible strategies were considered: implementing torrefaction first followed by leaching, or conducting leaching first followed by torrefaction. By incorporating both leaching and torrefaction treatments, regardless of order, a solid biofuel with improved properties was attained, especially in terms of higher heating value yield and ash melting temperature compared to individual treatment (either only torrefaction or only leaching). Depending on the sequencing of the leaching treatment, there was a reduction in ash yield from raw biomass ranging between 60% and 86%, while for torrefied biomass it was between 47% and 68%. Leaching treatment before torrefaction treatment was determined to be a more effective combination.